circRNA hsa_circ_0018414 inhibits the progression of LUAD by sponging miR-6807-3p and upregulating DKK1 - Yuanshan Yao; Yinjie Zhou; Qingwang Hua (Elsevier, 2021)
Lung adenocarcinoma (LUAD) is a subtype of lung cancer with a high incidence and mortality all over the world. In recent years, circular RNAs (circRNAs) have been verified to be a novel subtype of noncoding RNAs that exert vital functions in various cancers. Our research was designed to investigate the role of circ_0018414 in LUAD. We first observed that circ_0018414 was downregulated in LUAD tissues and cells. Also, low expression of circ_0018414 predicted unfavorable prognosis of LUAD patients. Then, upregulation of circ_0018414 repressed cell proliferation and stemness, while promoting cell apoptosis, in LUAD. Moreover, circ_0018414 overexpression enhanced the expression of its host gene, dickkopf WNT signaling pathway inhibitor 1 (DKK1), therefore inactivating the Wnt/β-catenin pathway. Additionally, circ_0018414 could sponge miR-6807-3p to protect DKK1 mRNA from miR-6807-3p-induced silencing, leading to DKK1 upregulation in LUAD cells. Finally, rescue assays proved that circ_0018414 inhibited the progression of LUAD via the miR-6807-3p/DKK1 axis-inactivated Wnt/β-catenin pathway. The findings in our work indicated circ_0018414 as a tumor inhibitor in LUAD, which might provide a new perspective for LUAD treatment.